Genomic Resources Notes accepted 1 February 2015 – 31 March 2015. (July 2015) - Genomic Resources Development Consortium; Arthofer, Wolfgang; Bertini, Laura; Caruso, Carla; Cicconardi, Francesco; Delph, Lynda F.; Fields, Peter D.; Ikeda, Minoru; Minegishi, Yuki; Proietti, Silvia; Ritthammer, Heike; Schlick‐Steiner, Birgit C.; et al.
Abstract This article documents the public availability of (i) raw transcriptome sequence data, assembled contigs and BLAST hits of the Antarctic plant Colobanthus quitensis grown in two different climatic conditions, (ii) the draft genome sequence data (raw reads, assembled contigs and unassembled reads) and RAD‐tag read data of the marbled flounder Pseudopleuronectes yokohamae, (iii) transcriptome resources from four white campion (Silene latifolia) individuals from two morphologically divergent populations and (iv) nuclear DNA markers from 454 sequencing of reduced representation libraries (RRL) based on amplified fragment length polymorphism (AFLP) PCR products of four species of ants in the genus Tetramorium.